Accelerating total body irradiation with large field modulated arc therapy in standard treatment rooms without additional equipment = Weiterentwicklung einer Ganzkörperbestrahlungstechnik in modulierter Rotationstechnik mit großen Feldern für Standardbestrahlungsräume ohne zusätzliches Equipment - Polednik, Martin; Ehmann, Michael (Strahlentherapie und Onkologie, 2015)
PurposeThe aim of this study was to develop a generic and ultra-efficient modulated arc technique for treatment with total body irradiation (TBI) without additional equipment in standard treatment rooms.MethodsA continuous gantry arc between 300° and 70° composed of 26 subarcs (5° per subarc) using a field size of 40 × 40 cm2 was used to perform the initial beam data measurements. The profile was measured parallel to the direction of gantry rotation at a constant depth of 9 cm (phantom thickness 18 cm). Beam data were measured for single 5° subarcs, dissecting the individual contribution of each subarc to a certain measurement point. The phantom was moved to 20 measurement positions along the profile. Then profile optimization was performed manually by varying the weighting factors of all segments until calculated doses at all points were within ± 1 %. Finally, the dose distribution of the modulated arc was verified in phantom thicknesses of 18 and 28 cm.ResultsThe measured profile showed a relative mean dose of 99.7 % [standard deviation (SD) 0.7 %)] over the length of 200 cm at a depth of 9 cm. The measured mean effective surface dose (at a depth of 2 cm) was 102.7 % (SD 2.1 %). The measurements in the 28 cm slab phantom revealed a mean dose of 95.9 % (SD 2.9 %) at a depth of 14 cm. The mean dose at a depth of 2 cm was 111.9 % (SD 4.1 %). Net beam-on-time for a 2 Gy fraction is approximately 8 min.ConclusionThis highly efficient modulated arc technique for TBI can replace conventional treatment techniques, providing a homogeneous dose distribution, dosimetric robustness, extremely fast delivery, and applicability in small treatment rooms, with no need for additional equipment.